Strain profile and size dependent electronic band structure of GeSn/SiSn quantum dots for optoelectronic application - Tan, Chuan Seng (2015)
We study self-assembled GeSn/SiSn quantum dots for optoelectronic application in the Silicon photonics domain. Valence force field and k.p methods are used to investigate the strain distribution and band structure with size effect.